KANK4 promotes arteriogenesis by potentiating VEGFR2 signaling in a TALIN-1-dependent manner: basic sciences - Zhang, Chonghe; He, Hao; Dai, Jianing; Li, Yunxia; He, Jing; Yang, Wu; Dai, Jialin; Han, Feng; Kong, Wenyan; Wang, Xiaohong; Zheng, Xiangjian; Zhou, Jing; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2022)
Background: - - Arteriogenesis plays a critical role in maintaining adequate tissue blood supply and is related to a favorable prognosis in arterial occlusive diseases. Strategies aimed at promoting arteriogenesis have thus far not been successful because the factors involved in arteriogenesis remain incompletely understood. Previous studies suggest that evolutionarily conserved KANK4 (KN motif and ankyrin repeat domain-containing proteins 4) might involve in vertebrate vessel development. However, how the KANK4 regulates vessel function remains unknown. We aim to determine the role of endothelial cell-specifically expressed KANK4 in arteriogenesis. - - Methods: - - The role of KANK4 in regulating arteriogenesis was evaluated using Kank4−/− and KANK4iECOE mice. Molecular mechanisms underlying KANK4-potentiated arteriogenesis were investigated by employing RNA transcriptomic profiling and mass spectrometry analysis. - - Results: - - By analyzing Kank4-EGFP reporter mice, we showed that KANK4 was specifically expressed in endothelial cells. In particular, KANK4 displayed a dynamic expression pattern from being ubiquitously expressed in all endothelial cells of the developing vasculature to being explicitly expressed in the endothelial cells of arterioles and arteries in matured vessels. In vitro microfluidic chip-based vascular morphology analysis and in vivo hindlimb ischemia assays using Kank4−/− and KANK4iECOE mice demonstrated that deletion of KANK4 impaired collateral artery growth and the recovery of blood perfusion, whereas KANK4 overexpression leads to increased vessel caliber and blood perfusion. Bulk RNA sequencing and Co-immunoprecipitation/mass spectrometry (Co-IP/MS) analysis identified that KANK4 promoted EC proliferation and collateral artery remodeling through coupling VEGFR2 (vascular endothelial growth factor receptor 2) to TALIN-1, which augmented the activation of the VEGFR2 signaling cascade. - - Conclusions: - - This study reveals a novel role for KANK4 in arteriogenesis in response to ischemia. KANK4 links VEGFR2 to TALIN-1, resulting in enhanced VEGFR2 activation and increased EC proliferation, highlighting that KANK4 is a potential therapeutic target for promoting arteriogenesis for arterial occlusive diseases.
Gesehen am 13.02.2024